Model Pembelajaran Terjemah Dzikir dan Do’a Bacaan Salat di Sekolah Dasar Islam Khoiru Ummah Malang - Zaky Mubarok (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Prayer which is a medium of worship between a servant and the Creator should be interpreted more deeply. Special attention is needed to understand the meaning of prayer readings when carrying it out. A person will be more solemn when performing prayers if they know what the meaning is that they are always reading. This study aims to describe the purpose and learning model of translating prayers and dhikr prayer readings at SD Islam Khoiru Ummah Malang. This study uses a qualitative approach with a case study type of research. The data collection techniques used are observation, in-depth interviews with research subjects, and documentation. The data obtained was then analyzed using three techniques, namely pattern matching, making explanations and time series analysis (Yin, 2009). The results obtained are, first, the purpose of learning to translate dhikr and prayer readings at SD Islam Khoiru Ummah is so that students are not only able to memorize prayer readings, but also understand the meaning contained in this noble prayer practice. Second, the learning model used is a conventional model with a teacher-centered approach and expository strategy. Teachers become learning centers with lecture and drill methods to ensure that the material is absorbed in students' memories.